Quality Analysis of Rubber Seed Shell Briquettes mixed with Goat Manure and Their Utilization to Construction LKPD IPA Integrated Shared Model on Environmentally Friendly Technology Materials - Setiani, Winda; Wardana, Rendy Wikrama; Sutarno, M; Uliyandari, Mellyta; Firdaus, Thoha (Universitas PGRI Semarang, 2024)
This study aims to make and test the quality of rubber seed shell briquettes with a mixture of goat manure and utilize the results to construct worksheet that can be used to support integrated science learning shared models on Environmentally Friendly Technology materials. This research method is an experiment in making and analyzing rubber seed shell briquettes mixed with goat manure and utilizing the results to construct worksheet. Data collection techniques are experiments, documentation and literature studies. Data analysis techniques in the following research are quantitative analysis techniques and qualitative analysis. The experimental group was divided into three groups, namely: A1 with a composition of 87% charcoal: 13% adhesive, A2 with a composition of 77% charcoal: 23% adhesive, and A3 with a composition of 97% charcoal: 3% adhesive. The percentage of charcoal is 50% rubber seed shell charcoal and 50% goat manure charcoal. Conclusion: The briquette test showed a ratio of 97% charcoal and 3% adhesive showed the best results with a calorific amount of 6287 kcal/kg. The context of briquettes can be used as science learning materials in the form of worksheet on environmentally friendly technology materials.